Incontinentia pigmenti, an x-linked dominant disorder, in a 2-year-old boy with Klinefelter syndrome - Abhilasha Williams; Laxmisha Chandrashekar; Vivi M Srivastava; Meera Thomas; Saban Horo; Renu George (Wolters Kluwer Medknow Publications, 2017)
Incontinentia pigmenti (IP) is a rare X-linked dominant disorder, in which skin lesions distributed along Blaschko's lines appear shortly after birth. Early lesions which are erythematous/bullous evolve over time into warty lesions, hyperpigmented swirls/macules, and atrophic hypopigmented streaks. Clinical features are heterogeneous. Abnormalities of the teeth, nails, hair, eyes, central nervous system, and breast may also be present. While intelligence is generally normal, varied degrees of intellectual disability/developmental delay have been reported. Lifespan is normal. IP is associated with mutations of the inhibitor of kappa light polypeptide gene enhancer in B cell, kinase gamma (IKBKG) gene on chromosome Xq28. This gene is involved in the activation of nuclear factor kappa B which protects cells against apoptosis; therefore, cells with IKBKG mutations are extremely susceptible to apoptosis. X-linked dominant disorders are lethal to male fetuses. Males who survive with IP either have mosaicism or an additional X chromosome (Klinefelter syndrome). We present a 22-month-old boy with IP and Klinefelter syndrome.